The role of a check-mark in step length adjustment in long jump - Makaruk, H.; Starzak, M.; López, J. L. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was to examine the effects of utilizing a check-mark on step length adjustment in long jump. Twelve male non-skilled jumpers (age 22±0.9 years, height 1.74±0.09 m, body mass 69±9 kg) with 3 years athletics experience volunteered in this research. Using a within-participant design, participants performed six jumps in two conditions: with and without the check-mark. Footfall variability, and then step length adjustment during approach run (ten final steps) were evaluated by the calculation of the standard deviation (SD) of the toe-to-board distances for analogous step of the approach run across each subject`s attempts. The Optojump Next (Microgate, Italy) was used in this study. Post hoc analysis showed that the footfall variability was significantly (p < 0.05) different from 6th to 1st step from the board for both the approach run conditions. In addition, pairwise analysis indicated that the take-off accuracy was significantly (p < 0.05) greater, and onset of step length adjustment was significantly (p < 0.05) earlier in the check-mark conditions than seen in non-check-mark conditions. The low skilled athletes or those with inconsistent pattern of gait regulation should employ the check-mark on the run-way during their training and competitions.